Pembelajaran Muhadatsah dengan Menggunakan Media Gambar Berseri Pada Siswa Marhalah Tiga ‘Aliyah Wisma Asuhan Yatim Nurul Huda Kartasura - Husniyah Miftahul Firdausi (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2022)
This research is motivated by the lack of student enthusiasm in speaking Arabic during Muhadatsah (conversation) learning among third-stage (marhalah tiga) students at Wisma Asuhan Yatim Nurul Huda Kartasura. This is due to the teacher’s use of lecture-based methods and the students’ limited Arabic vocabulary. The use of sequential picture media (media gambar berseri) aims to boost students’ enthusiasm and confidence through engaging and enjoyable learning activities. This study uses a classroom action research (CAR) approach with the spiral model of Kemmis and McTaggart. The research subjects consisted of six third-stage (marhalah tiga) students at Wisma Asuhan Yatim Nurul Huda Kartasura for the 2022–2023 academic year. The action consisted of two cycles (Cycle I and Cycle II), preceded by a pre-cycle. Data collection techniques included observation, interviews, test assessments, and documentation. Based on the research results, it was shown that the use of sequential picture media could increase student enthusiasm in speaking Arabic, with the following indicators of success: 1)During the learning process, students appeared enthusiastic about learning. 2)The students’ speaking ability in Arabic improved and increased compared to their previous results, with the average pre-test score of 65, increasing to 67.5 in Cycle I, and reaching 74 in Cycle II. 3)The completion percentage rose from 33% in the pre-test, remained 33% in Cycle I, and jumped to 83% in Cycle II. 4) The advantages of sequential picture media are that it is low-cost, easy to use in learning activities, simple to create, and increases student enthusiasm and motivation to speak using Arabic. 5) The drawbacks are that it primarily emphasizes visual perception, and the simple pictures may limit students’ expression of vocabulary.